Data sources for microeconometric risk and vulnerability assessments - Hoddinott, John F.; Quisumbing, Agnes R. (World Bank, 2003)
This "toolkit" is designed to assist practitioners undertaking vulnerability assessments by identifying data sources, assessing their suitability for risk and vulnerability measurement, and proposing suggestions for data collection to supplement existing sources. It complements "Methods for Microeconometric Risk and Vulnerability Assessments: A Review with Empirical Examples" (Hoddinott and Quisumbing 2003), which discusses techniques for assessing vulnerability and issues relating to their application. The emphasis in both toolkits is on quantitative, survey-based methods for vulnerability assessment, although this document will also discuss contextual methods similar to those used in livelihoods-based approaches. This paper draws heavily on papers and discussions at an International Food Policy Research Institute/World Bank (IFPRI/WB) Workshop on Risk and Vulnerability: Estimation and Policy Implications held at the International Food Policy Research Institute in September 2002." -- Back Cover